Methodology of specialized education services under an inclusive perspective in regular schools - Damázio, Mirlene Ferreira Macedo (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This article aims to discuss Special Education under an inclusive perspective, focusing on the methodology of Specialized Education Services (SES) in regular schools. The objective of this critical-collaborative action research is to cooperatively investigate service and teaching methodologies in order to understand them. The project is implemented and developed by fourteen professionals who work in the SES of elementary schools based in Dourados/MS. Eight schools belong to the town, four of them belong to the State and two of them are part of the University, which offers specialized services. The research is in process of application and its results are partial. There are many confusions and controversies about the "how" to carry out the SES within a regular school under an inclusive perspective. Therefore, we present important questions prompted by the first stage of the research involving the methodology of the services and the misconceptions about the SES, MRR and Special Education.